2022
DOI: 10.1097/md.0000000000030120
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of optional parenteral antimicrobial therapy for complicated skin and soft tissue infections: A systematic review and Bayesian network meta-analysis

Abstract: Background: Skin and soft tissue infections (SSTIs) carry significant economic burden, as well as morbidity and mortality, especially when caused by methicillin-resistant Staphylococcus aureus. This study aims to investigate the efficacy and safety of optional antimicrobial therapy for the treatment of complicated SSTIs (cSSTIs). Methods: We searched PubMed, Medline (Via Ovid SP), Embase (Via Ovid SP), and the Cochrane Central Register of Controlled Trials from their inception to March 22, 2021 for randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
3
1
Order By: Relevance
“…The findings are consistent with those of the Lan et al study results, which show that the clinical efficacy of omadacycline is not inferior to that of comparators in the treatment of acute bacterial infections in adult patients [ 29 ]. However, in a Bayesian network meta-analysis by Li et al [ 12 ], whose findings showed that omadacycline was associated with a higher rate of clinical and microbiological treatment success for the treatment of infection disease, our results contrasted that.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings are consistent with those of the Lan et al study results, which show that the clinical efficacy of omadacycline is not inferior to that of comparators in the treatment of acute bacterial infections in adult patients [ 29 ]. However, in a Bayesian network meta-analysis by Li et al [ 12 ], whose findings showed that omadacycline was associated with a higher rate of clinical and microbiological treatment success for the treatment of infection disease, our results contrasted that.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by O’Riordan et al [ 19 ] discovered AEs higher in omadacycline than linezolid (54% vs. 37%); and the risk of AEs was found to be higher in the omadacycline group than comparators in the studies by Stets et al [ 18 ] (41.1% vs. 48.5%) and Noel et al [ 16 ] (41.4% vs. 50.9%). And the study by Li et al found that omadacycline was associated with a moderate rank of AEs, compared to another optional antimicrobial [ 12 ]. But contrary to the Lan et al study [ 29 ] and the O’Riordan et al study [ 17 ], the study by Lan et al found no significant differences between omadacycline and comparators [ 29 ]; O’Riordan et al [ 17 ] discovered a similar safety profile (48.3% vs. 45.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis, including 48 randomised trials with 24,381 patients, evaluated 20 types of antimicrobial treatment modalities. Omadacycline was associated with the most significant beneficial effect [85 ▪ ].…”
Section: Introductionmentioning
confidence: 99%